SQSTM1/p62 Controls mtDNA Expression and Participates in Mitochondrial Energetic Adaption via MRPL12 - Yuan Ma; Suwei Zhu; Tingting Lv; Xia Gu; Hong Feng; Junhui Zhen; Wei Xin; Qiang Wan (iScience, 2020)
Summary: Mitochondrial DNA (mtDNA) encodes thirteen core components of OXPHOS complexes, and its steady expression is crucial for cellular energy homeostasis. However, the regulation of mtDNA expression machinery, along with its sensing mechanism to energetic stresses, is not fully understood. Here, we identified SQSTM1/p62 as an important regulator of mtDNA expression machinery, which could effectively induce mtDNA expression and the effects were mediated by p38-dependent upregulation of mitochondrial ribosomal protein L12 (MRPL12) in renal tubular epithelial cells (TECs), a highly energy-demanding cell type related to OXPHOS. We further identified a direct binding site within the MRPL12 promoter to ATF2, the downstream effector of p38. Besides, SQSTM1/p62-induced mtDNA expression is involved in both serum deprivation and hypoxia-induced mitochondrial response, which was further highlighted by kidney injury phenotype of TECs-specific SQSTM1/p62 knockout mice. Collectively, these data suggest that SQSTM1/p62 is a key regulator and energetic sensor of mtDNA expression machinery.